(untitled) (Texas Journal of Medical Science, 2022)
Chronic heart failure (CHF) and obesity are widespread in the population and often coexist, increasing the risk of complications in this category of patients. In patients with heart failure (HF), the prevalence of obesity is 32-49%. At the same time, most of the patients are pre-represented by persons with HF and a preserved LV ejection fraction. Obesity is an independent risk factor for heart failure. It is shown that as the body mass index increases for every 1 kg/m2 , the risk of developing HF increases by 7% in women and 5% in men. Chronic heart failure (CHF) and obesity are widespread in the population and often coexist, increasing the risk of complications in this category of patients. In patients with heart failure (CHF), the prevalence of obesity is 32-49%. At the same time, most of the patients are represented by persons with HF and a preserved LV ejection fraction. Obesity is an independent risk factor for heart failure. It has been shown that as the body mass index (BMI) increases for every 1 kg/m2 , the risk of developing HF increases by 7% in women and by 5% in men. Obesity has become a worldwide epidemic, and its prevalence is projected to increase by 40% in the next decade. The growing prevalence of obesity has an impact on the risk of developing diabetes mellitus, cardiovascular diseases, as well as chronic kidney disease (CKD). A high body mass index is one of the most significant risk factors for CKD. In obese individuals, compensatory hyperfiltration develops in response to an increase in the metabolic needs of overweight. An increase in intraclubular pressure can lead to kidney damage and an increased risk of developing CKD in the long term. In recent years, the incidence of glomerulopathy associated with obesity has increased 10-fold. In addition, obesity has been shown to be a risk factor for nephrolithiasis and a number of malignant neoplasms, including kidney cancer.